2021
DOI: 10.1002/pat.5482
|View full text |Cite
|
Sign up to set email alerts
|

Structures and properties of polymers in ion exchange membranes for hydrogen generation by water electrolysis

Abstract: Water electrolysis (WE) is an electrochemical process that splits water and forms hydrogen and oxygen, in presence of catalyst. This is a rapidly developing technology owing to its extreme importance in the generation of hydrogen. Membrane-based WE involves the use of anion exchange, proton exchange and bipolar membranes, among which the anion exchange membrane-based WE technology is in the most advanced stage, followed by the proton exchange membrane-based WE. While, the bipolar membrane-based WE is the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 107 publications
(180 reference statements)
0
11
0
Order By: Relevance
“…In addition, PF is easily obtained as the sufficiently high‐molecular weight with narrow polydispersity by the Suzuki‐Miyaura coupling polymerization. As the Suzuki‐Miyaura cross‐coupling of organodiboronic acid and organodihalides gives alternating copolymers, the IEC of the AEM can be selected by changing the combination of monomers 35 . The alkyl spacer between the polymer main chain and ion exchange groups is another crucial molecular design point.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, PF is easily obtained as the sufficiently high‐molecular weight with narrow polydispersity by the Suzuki‐Miyaura coupling polymerization. As the Suzuki‐Miyaura cross‐coupling of organodiboronic acid and organodihalides gives alternating copolymers, the IEC of the AEM can be selected by changing the combination of monomers 35 . The alkyl spacer between the polymer main chain and ion exchange groups is another crucial molecular design point.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, aromatic polymers with no heteroatom bonds in the polymer main chain are expected to show high chemical stability. For the study of polymer electrolyte fuel cells using AEMs, polyphenylene‐type and polyfluorene‐type AEMs have been reported as the desired main chains with high‐chemical stabilities 21,33–37 . Bae et al reported that AEMs with a terphenyl backbone with high‐alkaline stability maintain ion exchange capacity (IEC) even after immersion in an basic aqueous solution (1 M NaOH) at 95°C for 60 days 38 .…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Hydrogen, as a promising energy carrier, plays a significant role in the carbon-neutrality world because of its various advantages: sustainability, nontoxicity, and high energy contents. [3,4] The use of hydrogen mitigates the environmental impacts that occur with carbon-based fuels. However, unlike fossil fuels, hydrogen as a form of fuel is not available to use in nature.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17] The recent development of AEM and anion-exchange ionomers for AEM-WE or AEM fuel cell application was reviewed in Refs. [18][19][20][21][22]. Particularly, AEMs developed for AEM-WE application were summarized in Refs.…”
mentioning
confidence: 99%
“…[20] In Ref. [21], a comprehensive Review related to the structures and properties of polymers in anion and cation exchange membranes for water electrolysis application is presented. Advances in AEMs for fuel cells and electrolyzers application were also presented by Mandal.…”
mentioning
confidence: 99%